2021
DOI: 10.1038/s41467-021-20980-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving hindlimb locomotor function by Non-invasive AAV-mediated manipulations of propriospinal neurons in mice with complete spinal cord injury

Abstract: After complete spinal cord injuries (SCI), spinal segments below the lesion maintain inter-segmental communication via the intraspinal propriospinal network. However, it is unknown whether selective manipulation of these circuits can restore locomotor function in the absence of brain-derived inputs. By taking advantage of the compromised blood-spinal cord barrier following SCI, we optimized a set of procedures in which AAV9 vectors administered via the tail vein efficiently transduce neurons in lesion-adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 73 publications
2
53
0
Order By: Relevance
“…Spinal cord injury (SCI) causes locomotor dysfunction by severing the supraspinal connections as well as disrupting the neuronal network in spinal CPG 17 , 18 . Restoration of accurate locomotion requires reestablishment of neural circuits in spinal CPG 19 . The paucity of regrowth of injured axons in the adult mammalian central nervous system (CNS) is a major hurdle in understanding the intrinsic mechanisms that promote appropriate axon regrowth.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) causes locomotor dysfunction by severing the supraspinal connections as well as disrupting the neuronal network in spinal CPG 17 , 18 . Restoration of accurate locomotion requires reestablishment of neural circuits in spinal CPG 19 . The paucity of regrowth of injured axons in the adult mammalian central nervous system (CNS) is a major hurdle in understanding the intrinsic mechanisms that promote appropriate axon regrowth.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the BSCB is restored within 7 days post-SCI 9 , and this prevents macromolecular agent from penetrating in the late stage of SCI 39 . Fortunately, the restored BSCB still allows the penetration of small molecules or specific peptides or proteins 40 .…”
Section: The Nanodrug Delivery System Could Deliver Small Molecules T...mentioning
confidence: 99%
“…However, a hurdle to the application of these treatments [12][13][14][15] for CNS diseases such as SCI is that these agents cannot easily enter the CNS because of blood brain barrier (BBB) or brain spinal cord barrier (BSCB). In this regard, a recent study showed that BSCB disruption permits intravenously injected AAV9 to enter the injured spinal cord 9 . Although the underlying mechanism of injury-induced BSCB alterations remains unknown, this finding suggests the exciting possibility of designing relevant agents that can enter the spinal cord lesion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations